Design of a Negative Voltage Generator circuit in 180nm technology - Mahmood, Saad (2024)
An on-chip Negative Voltage Generator block has been designed in 180nm silicon technology to produce a negative voltage rail for circuits that require biasing below ground. A switched capacitor circuit known as a charge pump inverter generates the negative voltage, however, due to its switching nature and non-zero output resistance, the produced voltage rail has its ripple and average value dependent on the load. A linear regulator is used to stabilise this negative voltage, and the voltage ripple is filtered by the power supply rejection of the regulation loop. The charge pump inverter designed can generate approximately -10V from a +12V rail in less than 1ms with an output resistance of 33Ω. The linear regulator regulates the charge pump’s negative voltage output to -7V with a ripple rejection of 35dB, phase margin better than 60-degree, line-regulation of 6mV/1V and load-regulation of 0.2mV/mA. The methodology, key design decisions, system trade-offs and achieved results are discussed in this master thesis report.